Microbial Conversion Of Sago Sugars Into Lactic Acid - Kopli, Bujang (2011)
In Malaysia, most sago palm estates are found in Sarawak, where peat swamp covers about 75% of the state (Adeni and Bujang, 1998; Bujang et al., 2001). The number of sago palm plantations has increased due to emergence of subsidized plantations by the state government along with the existing wild stands in the coastal area. Sago palm (Metroxylon sagu) is able to thrive in swampy areas and grows naturally without the need for pesticide and herbicide (Pei-Lang et al., 2006). In Sarawak, the production of sago starch is reported to be approximately 2-5 tons/ha and 10-25 tons/ha for uncultivated (wild) regions and sago palm plantation, respectively. In order to sustain the systematical exploration of sago resource along with providing sufficient amount of sago palm for increasing demand of sago starch in the global market, the state government of Sarawak has instigated two large plantations located at Dalat and Mukah districts at a total of 22,000 ha (Singhal et al., 2008). Previous estimation revealed that a sago palm plantation can yield up to 25 tons of sago starch/yr/ha, contributing as the main starch source for the food and industrial products (Ishizaki, 1997). Sago starch is used in the production of food delicacies such as noodles, cookies, fish crackers, syrups, fructose and monosodium glutamate (MSG). Sago starch has also been used as adhesives and can be potentially used as the main substrate in the production of ethanol, lactic acid, kojic acid, cyclodextrin (CD) and biodegradable polymers (Bujang and Ahmad, 2000; Singhal et al., 2008.).